EFFECT OF COMMUNICATION BETWEEN PRIVATE AND STUDENT ACHIEVEMENT MOTIVATION TO LEARN CASE STUDY OF SMK NEGERI YOGYAKARTA 7 - Subardiyani, Rika; Kholisoh, Dr. Luluk; Septi W.,S.E.,MM, Helly (Management, 2010)
Research thesis entitled The Effect of Inter Personal Communication and Student Motivation Student Achievement Against SMK N 7 Yogyakarta, Jl. South Gowongan Jt. III/416 Yogyakarta, carried out from January to March 2010 with the respondent student of SMK Negeri 7 Yogyakarta. This thesis research aims to determine whether the Inter Personal Communication and Motivation Achievement Student Learning affect SMK N 7 Yogyakarta. Data collection method used in this research is data collection and dissemination of a questionnaire. While the methods of data analysis used in this research is descriptive analysis method and quantitative measurement method which can be expressed with numbers. Based on the analysis of multiple linear regression equation premises t test results can be seen that the interpersonal communication variables affect student achievement by t test bigger than t table (2.753> 1.994) and learning motivation variables influencing student achievement with the t test bigger than t table (2.197 > 1.994). In Fcount test can also be seen that the variable of interpersonal communication and motivation to study jointly affect student achievement with value F count is greater than F table (4.607> 3.129). Among the variables tested was variable Inter-Personal Communication has the highest value (dominant) that is equal to 2.753 compared with the variables affecting Achievement Motivation in Student Learning with a beta coefficient of 0.278 larger than the variable with a value of 0.135 Learning Motivation. Student achievement is significantly influenced by the Inter Personal Communication and Motivation Learning with a value of 0.345 or 34.5% while the remaining 0.655 or equal to 65.5% influenced by other variables not included in this study. Keywords: learning motivation, communication, achievement.